Öğretmenlerin Mesleki Deneyimlerinin İncelenmesi: Öğretmen Olmanın Anlamına İlişkin Fenomenolojik Bir Çalışma / Phenomenological Research on the Meaning of Being a Teacher - Koşar, Didem (Journal of History Culture and Art Research, 2019)
Abstract The aim of this research was to analyze how teachers make sense of being a teacher depending on their professional experiences. This research was designed in descriptive phenomenological design under the qualitative research method that focuses on determining how teachers make sense of teaching experiences. Criterion sampling and maximum variation sampling under purposeful sampling methods were conducted to select the participant of the present study. The data of the study were gathered through a semi-structured interview form including open-ended questions developed by the researcher. A systematic process composed of the steps entitled bracketing, phenomenological reduction, imaginative variation and synthesizing of meanings and essences was conducted to analyze the data. Results revealed that being a teacher was composed of six interrelated components entitled touching the lives of the others, being versatile, self-renewal, guiding, providing new perspectives and struggling with difficulties. The results of the research were discussed in line with the related literature. Öz Bu araştırmanın amacı, öğretmenlerin mesleki deneyimlerine dayalı olarak öğretmenliğe nasıl anlam yüklediklerini incelemektir. Araştırma, nitel araştırma yöntemi ve betimsel fenomenolojik desende yürütülmüştür. Çalışma grubunun belirlenmesinde amaçlı örnekleme yöntemlerinden ölçüt örnekleme ve maksimum çeşitlilik örneklemesi kullanılmıştır. Araştırmada verilerin toplanması amacıyla araştırmacı tarafından geliştirilen ve açık uçlu sorulardan oluşan yarı yapılandırılmış görüşme formu kullanılmıştır. Araştırma verilerinin analizinde parantezleme, fenomenolojik redüksiyon, imgesel çeşitleme ve anlam ve özlerin sentezlenmesi basamaklarından oluşan bir süreç takip edilmiştir. Araştırma sonuçları öğretmenlerin deneyimlerinden hareketle öğretmenliğin hayata dokunma, çok yönlü olma, kendini yenileme, yol gösterme, ufuk açma, zorluklarla mücadele edebilme olmak üzere altı temel bileşenden oluştuğunu ortaya koymaktadır. Araştırma sonuçları, ilgili alan yazın doğrultusunda tartışılmıştır.